The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/ajp.0b013e318156ca63
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Assessment of Sleep in Adolescents With Chronic Pain Compared to Healthy Adolescents

Abstract: Adolescents with chronic pain evidenced poorer sleep quality, increased insomnia symptoms, and less efficient sleep with more wake bouts in comparison with healthy adolescents, findings that require replication in a larger sample. Assessment and management of sleep disturbances is an important aspect of care for children and adolescents with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
88
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 44 publications
(38 reference statements)
10
88
2
1
Order By: Relevance
“…In adolescence, physical and mental health, as well as school performance and quality of life can be affected by pain [2,[8][9][10][11][12]. Studies that have assessed functional status via questionnaires have found that pain can also impair activities of daily functioning [13][14][15]. Physical inactivity has major health effects worldwide, causing noncommunicable diseases such as cardiovascular disease, diabetes, cancer, and depression [16].…”
Section: Introductionmentioning
confidence: 98%
“…In adolescence, physical and mental health, as well as school performance and quality of life can be affected by pain [2,[8][9][10][11][12]. Studies that have assessed functional status via questionnaires have found that pain can also impair activities of daily functioning [13][14][15]. Physical inactivity has major health effects worldwide, causing noncommunicable diseases such as cardiovascular disease, diabetes, cancer, and depression [16].…”
Section: Introductionmentioning
confidence: 98%
“…Sleep quality and duration are interlinked concepts 12 and can be assessed objectively or subjectively. Empirical evidence has shown that subjective assessment of sleep is more sensitive to difference in sleep patterns 13 and had stronger correlation with clinical conditions 14 (eg, depression) than objective measurements such as polysomnography and actigraphy. 15 It has been well documented that self-reported poor sleep quality or extreme sleep durations (either too short or too long) are related to a wide spectrum of health outcomes of older people, including cognitive impairment, depressive symptoms, physical functioning, mobility disorder, pain, and vitality.…”
Section: Introductionmentioning
confidence: 99%
“…We assessed sleep behaviorally using actigraphy and focused specifically on sleep duration, sleep efficiency, and sleep latency because these sleep parameters have been associated with health-relevant outcomes (e.g., prehypertension, parasympathetic functioning, pain, inflammation, insulin resistance) among youth (Hall et al, 2015; Javaheri et al, 2008; Matthews et al, 2012; Michels et al, 2013; Palermo et al, 2007; Rodríguez-Colón et al, 2015). We conceptualize sleep on a continuum, and use the term “poor sleep” to refer to shorter sleep duration, lower sleep efficiency, and longer sleep latency, as has been done in previous research (Doane and Thurston, 2014; Kahlhöfer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%